Faktor-faktor yang mempengaruhi keputusan investasi pada instrumen saham - Firmansah, Rendy; Irawan, Muhammad Agus; Cahya, Bayu Tri (Islamic Accounting Journal, 2024)
This study is to examine the effect of financial literacy, financial behavior, capital market training, minimum investment capital, and social media as a source of information on investment decisions in stock instruments. Stocks are an investment option that is increasingly attracting public attention, this cannot be separated from the high profit potential of stock investment despite the high risk that accompanies it. The rapid advancement of technology makes it easier for people to invest because it can be done anywhere and anytime. FEBI IAIN Kudus students are one of the parties who study economics in depth, providing advantages in terms of awareness of the importance of investment and becoming a hope to become successful investors in the Indonesian capital market. This study involved students of the Faculty of Economics and Islamic Business of IAIN Kudus as respondents. Data collection was carried out using a questionnaire and data analysis techniques in this study using the help of the SPSS 26 application. The results showed that financial literacy, minimum investment capital, and social media have a significant influence on stock investment decisions. Meanwhile, financial behaviour and capital market training do not have a significant effect. This study illustrates that increasing financial literacy, easy access to information through social media, and a more affordable minimum capital policy can encourage better investment decisions among students.